Do monetary policy and macroeconomic fundamentals matter under high uncertainty? Evidence from Renminbi exchange rate regimes - Zhang, Mengdi; Chin, Lee; Wan Ngah Wan, Azman Saini (Universitas Islam Indonesia, 2026)
Purpose — This study examines the nonlinear effect of Economic Policy Uncertainty (EPU) on China’s Renminbi (RMB) exchange rate. Methods — Based on the monetary model of exchange rate determination and the behavioural equilibrium exchange rate model, a threshold autoregressive model was estimated with EPU as the threshold variable. Quarterly data from Q1 2005 to Q4 2023 were utilised. Finding — Under different regimes, the effects of EPU, monetary factors, and macroeconomic factors on the exchange rate are nonlinear. The study also reveals significant differences in the volatility characteristics of exchange rate misalignment under low and high EPU conditions, supporting the hypothesis that EPU has a nonlinear impact on the exchange rate. Furthermore, when EPU is low, external shocks exert a stronger impact on the exchange rate than when EPU is high. Implications — These results suggest that governments and policymakers can help investors anticipate market shifts by increasing policy transparency and reducing unnecessary policy changes, thereby maintaining economic stability.Originality — By integrating EPU into a framework combining the monetary model and the BEER model and estimating a nonlinear threshold model, this study provides new evidence on exchange rate dynamics and misalignment under varying EPU regimes